Landlords’ perception on the introduction of the Residential Tenancy Act (RTA) - Mohamed Osman, Mariana; Shuid, Syafiee; Azmi, Nurul Ardila (2019)
Deficiency of firm regulations administering the tenancy process has resulted in recurred disputes over a long span of years. This study analyzed the landlord's perception on the introduction of the Residential Tenancy Act (RTA) by examining landlords' acceptance or refusal. This study applied the descriptive analysis method on 50 questionnaire surveys distributed to landlords in Gombak district. Results showed that 70% of the respondents agreed on the introduction of RTA, while deposit payment is the most preferred principal concept to be consolidated in RTA. These results have recommended strategies to boost the landlord's acceptance of RTA.